PEMBENTUKAN KARAKTER BAGI ANAK USIA 4-6 TAHUN MELALUI METODE BERCERITA DENGAN AUDIO VISUAL - Lina Kamalia Zahra; Arri Handayani; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Early childhood is a child who has just been born until the age of 6 years. Early age is a very crucial age for the formation of a child's character and personality. Children's character formation should be done from the golden age. Where at that age children can think and judge the things they see or hear. As time goes by, children spend more and more of their free time playing with gadgets, so interaction with friends or people around them decreases. Children tend to have negative characters, become closed individuals, like to be alone, and have violent behavior. Facing this problem, educators and parents should look for ways so that children can always grow and develop into children with good personalities, through various methods. One of the methods used is inserting a moral message through storytelling. The storytelling method using audio-visuals is interesting for children and can increase children's interest in listening to stories. Parents or educators can tell stories of characters with good character. Good character formation can be done by emulating their idol characters through the audiovisuals they see. It is hoped that children will be motivated and imitate the characters in the story. It is hoped that the audio-visual storytelling method can be used to build character at an early age.